Heterogeneous informality in Costa Rica and Nicaragua - Enrique Alaniz; Thomas Gindling; Catherine Mata; Diego Rojas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Informal work is often considered a place of employment for marginalized and vulnerable workers who have been rationed out of preferred formal work. However, informality can also be seen as a dynamic sector that budding entrepreneurs and those looking for flexible working conditions enter voluntarily. We use the methodology developed in Günther and Launov (2012) to test for the voluntary and involuntary nature of informal work in Nicaragua and Costa Rica, without making ad hoc assumptions about labour market segmentation and self-selection. We find evidence of heterogeneous informality in both Nicaragua and Costa Rica, with one informal sub-segment where most workers are voluntarily informal and another informal subsegment where most workers are involuntarily informal. In Nicaragua, our results suggest that 44 per cent of wage employees are involuntarily informal, while 30 per cent of self-employed workers are involuntarily informal. In Costa Rica, our results suggest that 10 per cent of wage employees are involuntarily informal, and that 66 per cent of the self-employed are involuntarily informal.
Keywords: F63; J8; J32; J46; 330; involuntary informality; developing economies; finite mixture model; Costa Rica; Nicaragua